GALERI ATSIRI INDONESIA - Egahny, Elena Stefani; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Essential oils or known as essential oils, ethereal oils, or volatile oils. Essential oils have benefits, including as a basic ingredient in fragrances in the perfume, cosmetic, persian (flavor) and pharmaceutical industries with their anti-bacterial, sanitary and aromatherapy functions. Because of the many uses, many essential oils are imported at the request of foreigners, while they are still very little used. Therefore, Dewan Atsiri Indonesia is trying to increase the introduction of essential oils in Indonesia. Therefore, the designer wants to educate the general public about the essential oil industry through space and architecture through an analogy approach.